Analisis Intervensi Teknologi Umur Bibit, Jajar Legowo, dan Pemupukan Urea Terhadap Produksi Padi - Hariyanto, Wahyudi (Informatika Pertanian, 2015)
Technology of ICM (Integrated Crop Management) has been introduced to farmers since 2002, but farmers have not applied it until now.The problem is the slow dissemination process, and farmers are still low in implementing some components of ICM. Technology intervention is needed to increase production and productivity. This study aimed to analyze the relationship between seed maturity, jajar legowo and urea fertilizers on rice production. The experiment was conducted in Banyuasin October-December 2012. The method used was observation and FGD (Focus Group Discussion) against ICM field school in Banyumas. The study population totaled 300 farmers spread over the District ICM field school location. The sample was 70 farmers taken by using Slovin formula. Data were analyzed using path analysis. The results showed that the jajar legowo affected rice production by 12.2%, and the use of urea fertilizer by 26.3%. while seed maturity did not have significant effect. Combined together, both technologies affected rice production by 38.5%. It was suggested to implement ICM technology as recommended.